PENGARUH BOKASHI KOTORAN SAPI DAN PUPUK FOSFAT TERHADAP MUTU FISIOLOGIS BENIH KEDELAI (Glycine max L. Merill) KULTIVAR GROBOGAN - Wulandari M M; Sumadi .; M Kadapi (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2017)
The most important increasing productivity soybean in physiological quality of seed. There for, soybean cultivation also improving soil quality for increase yield and seed quality. This research was aimed to obtain the best combination doses of bokashi cattle manure and phosphate fertilizer on yield and seed quality. This research was held at Faculty of Agriculture Padjadjaran University experimental garden in Sumedang regency and Seed Technology Labotary from November 2016 to Februari 2017. The design that used in this research was Randomized Completely Block Design and Scott-Knott at 5% rate. Treatment used in this research were Grobogan cultivars with tested combinations doses bokashi 0 t ha-1, 16 t ha-1, 32 t ha-1 and 48 t ha-1, each combined with (SP-18) doses 0 kg ha-1, 16 kg ha-1, 32 kg ha-1 and 48 kg ha-1 which were repeated three times. The result of experiment indicated significantly for weight 100 grains and quality of seed. This experiment suggested that dosage of 48ton/ha bokashi cattle manure and 32 kg ha-1 phosphate fertilizer in the best combinations of soybean crop.Keywords: Bokashi, Phosphate fertilizer, Physiological quality, Soybean seed